Digital practice spaces and clinical practice in teacher preparation: Current uses and future possibilities. Issue 1 (1st January 2021) - Littenberg-Tobias, Joshua; Kaka, Sarah; Kessner, Taylor; Tuf Francis, Anthony; Kennett, Katrina; Reich, Justin
Abstract: This paper explores how the use of digital practice spaces (DPSs) can inform teacher preparation through a reimagining of clinical practice in teacher preparation by addressing the question: what roles might DPSs play in the ecology of apprenticeship opportunities for future educators? We leveraged AACTE's Essential Proclamations and Tenets for Highly Effective Clinical Educator Preparation as an analytical framework to examine our own experiences using DPSs in our teacher education coursework. We discuss the alignment between these proclamations and the theoretical, conceptual, and practical underpinnings of DPSs. Finally, we consider the remaining proclamations that represent the horizons of DPSs within teacher preparation, a task we undertook as a set of informed provocations, envisioning how DPSs could be designed to support the proclamations not currently supported.